PENGARUH TINGKAT PENDIDIKAN, MASA KERJA DAN MOTIVASI KERJA TERHADAP KINERJA DAN KOMPETENSI SEBAGAI VARIABEL INTERVENING PEGAWAI KANTOR PELAYANAN PAJAK PRATAMA WATES - Muhammad Fahmi; Muhammad Mathori (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2023)
This study aims to examine and analyze the effect of level of education, work period and work motivation on employee performance with competence as an intervening variable in for employees of Wates Tax Office with respondents as many as 82 employees. This study uses a quantitative and survey approach. Data collection is done using the questionnaire method. Data analysis method using descriptive statistical analysis and Test with Partial Least Square (PLS). The results of this study show that competence able to explain significantly negative influences the level of education on employee performance, competence e is not effective enough to explain the influence of work period on employee performance, and competence able to explain significantly positive influence the work motivation on employee performance.